Focal Muscle Vibration Method Application in Recovery of the Upper Limb Function in Patients with Cerebral Stroke in the Early Recovery Period - Olga V. Fuchizhi; Marina A. Shurupova; Galina E. Ivanova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Motor disorders as a result of stroke impair the mobility of the patient, limiting his participation in daily activities. Spastic paresis is one of the most frequent consequences of the central nervous system damage. At present, a promising method of therapy for spastic paresis,due to its non-invasiveness and safety, is the application of focal muscle vibration (FMV) in stroke patients. Foreign studies demonstrate the successful use of FMV, while there are no mentions of the FMV application of in the Russian literature. Aim. To evaluate the effectiveness of the of FMV use in the rehabilitation of the upper limb in the early recovery period in patients who have suffered a cerebral stroke, with a degree of disability of 3 points on the Rankin scale. Material and methods. The study involved 40 patients of the Federal Center of Brain Research and Neurotechnologies: 20 patients of the experimental group (13 men, 51.4±12.85 years) and 20 patients of the control group (15 men, 53.0±11.34 years). Patients of the control group received a course of conventional physical therapy (individual physical therapy sessions). The participants of the experimental group, in addition to conventional physical therapy classes identical to those in the control group, underwent a training course on the «Vibramoov» (Techno Concept, France) apparatus for the upper limb. To assess the effectiveness of rehabilitation before and after the course, functional scales (MRC, MAS, FMA, FAT) were used to assess the degree of the upper limb functional recovery. Results and discussion. As a result, the patients of the experimental group showed improvements in both the proximal and distal parts of the upper limb, while the patients of the control group only in the proximal. Conclusion. Due to the results obtained after the course with the use of FMV, the range of motor skills has expanded in patients that will allow them to use the upper limb more effectively when performing household activities, such as eating, dressing, personal hygiene, etc.